SIGNIFIKANSI INFORMASI ISU KEBOCORAN DATA PRIVASI TOKOPEDIA TERHADAP PERILAKU FANDOM - Azziza Ratri Pradina; Radita Gora Tayibnafis; Vinta Sevilla (Universitas Prof. Dr. Moestopo (Beragama), 2022)
This research is motivated by the case of user privacy data leaks experienced by Tokopedia in 2020. This study aims to see the effect of information about the leakage of user data experienced by Tokopedia on the behavior of the audience studied using attribution theory. The method used in this research is quantitative explanatory to explain the causal relationship between variables. Information data leakage is measured by its quality value and consists of four characteristics, namely accurate, timeless, relevant, and complete, while audience behavior is measured by attribution theory based on internal factors and external factors, namely paying attention to the principle of consensus, the principle of consistency and the principle of distinctiveness. The results of this study explain that Ha is accepted and H0 is rejected so that the quality of information about Tokopedia user data leakage affects people's behavior. Information about the leakage of Tokopedia user data received by the public is of good quality, and internal factors influence the audience's behavior. The conclusion of this study explains that there is an influence between the leakage of Tokopedia user data and the behavior of the audience with a value of 0.341 at a low level of relationship.